Medicinal Plant Research in Ayurveda: A Scientific Review of Traditional and Modern Applications - Mr. Praveen Sisodya; Prof. (Dr.) Gaurav Dubay; Prof. (Dr.) Umesh Kumar Gilhotra (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Ayurvedic medicine is a millennial health system practised in India since more than 3000 years ago, and makes use of a huge variety of plant materials to medicate themselves. The given review examines the historical role, type of classification, and pharmacology characteristics of Ayurvedic medical plants, along with their contemporary uses. We discuss the classical Ayurvedic system of classifying plants, which is in terms of taste (Rasa), intrinsic qualities (Guna), potency (Virya), post-digestive effect (Vipaka) and special qualities (Prabhava). The review also points at significant bioactive compounds, including curcumin, withanolides, and bacosides, speaking about their antioxidant, anti-inflammatory, and neuroprotective properties. Besides, we consider the spatial distribution of the most popular Ayurvedic plants along with their role shown both in the past and nowadays. This is also the case of integrating Ayurveda and modern scientific methods such as standardization, quality control, and biotechnology development. Regulatory, scientific validation, and sustainability issues continue to be an obstacle in spite of the promising prospects. The purpose of the review is to give a full picture of medicinal plants of Ayurveda leading to interdisciplinary cooperation in future studies and clinical practice.